ANALISIS PERANAN POLA ASUH ORANG TUA DALAM MEMOTIVASI BELAJAR SISWA - Siti Isma Nurfarija, - (2021)
Parents are the first place of education for children in the formation of a child's personal. Family is an informal education that plays an important role in motivating students' learning. The goal in this study is to find out how parenting in motivating student learning and knowing the obstacles and solutions of parents in motivating student learning. Using qualitative approaches and methods of literature studies. The results of this study show that parents who apply good parenting and in accordance with the child's development and can provide a supportive role in motivating student learning are parents who apply authoritative or democratic parenting. This democratic parenting is able to give encouragement to children to have high learning motivation and good social attitudes. Then the obstacles that occur in parents, namely due to the age of parents, lack of firmness from parents, economic factors, lack of parental awareness in applying good parenting, lack of understanding and cohesiveness of parents in applying parenting, and less conducive living conditions. And the solution that parents can do to overcome these obstacles, namely parents realize that their role determines student success and is influential in motivating students to learn hard, control and supervise children, spend time in the midst of busyness, support and continue to give students full motivation in learning and things that are in demand by students, understand the characteristics of the child and the abilities possessed by the child, as well as working with families and communities in the living environment to create a conducive and comfortable atmosphere for learning.